Wind Bands and Cultural Identity in Japanese Schools - Hebert, David G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
This well researched volume tells the story of music education in Japan and of the wind band contest organized by the All-Japan Band Association. Identified here for the first time as the world$1 (Bs largest musical competition, it attracts 14,000 bands and well over 500,000 competitors. The book$1 (Bs insightful contribution to our understanding of both music and education chronicles music learning in Japanese schools and communities. It examines the contest from a range of perspectives, including those of policy makers, adjudicators, conductors and young musicians. The book is an illuminating window on the world of Japanese wind bands, a unique hybrid tradition that comingles contemporary western idioms with traditional Japanese influences. In addition to its social history of Japanese school music programs, it shows how participation in Japanese school bands contributes to students$1 (Bsense of identity, and sheds new light on the process of learning to play European orchestral instruments.s
Foreword -- Part I: A social history of wind bands in Japanese schools. Chapter 1: Introduction -- Chapter 2: Where are these bands from? -- Part II: An ethnography of wind bands in Japanese schools. Chapter 3: An invitation to the Tokyo middle school -- Chapter 4: The band rehearsal ritual and its participants -- Chapter 5: Instruction in the Japanese school band -- Chapter 6: Scenes from the 50th AJBA national band competition -- Chapter 7: Winning in the band: Views from beneath and within -- Chapter 8: Winning in the band: Views from above and beyond -- Chapter 9: Japanese composers and wind band repertoire -- Chapter 10: Leadership and duty in the ensemble -- Chapter 11: Cooperative learning and mentorship in band -- Chapter 12: Organizational training of the Japanese band director -- Chapter 13: Corporate giants -- Chapter 14: Metaphors of a Japanese band community -- Chapter 15: Musical identity in the band -- Chapter 16: National identity in the Japanese school band -- Chapter 17: Ensemble ethos -- Chapter 18: Conclusions -- Afterword -- Glossary -- Bibliography -- Index.
Keywords: Education; Culture -- Study and teaching; Art education; Education; Arts Education; Regional and Cultural Studies; Electronic books